2021
DOI: 10.1038/s41467-021-25694-1
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome in konzo

Abstract: Konzo, a distinct upper motor neuron disease associated with a cyanogenic diet and chronic malnutrition, predominately affects children and women of childbearing age in sub-Saharan Africa. While the exact biological mechanisms that cause this disease have largely remained elusive, host-genetics and environmental components such as the gut microbiome have been implicated. Using a large study population of 180 individuals from the Democratic Republic of the Congo, where konzo is most frequent, we investigate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Our systematic evaluation of strategies to jointly analyze microbiome and metabolome data has permitted the illustration of the best methods depending on the research question. Thus, through an application on metabolomics and metagenomics data of the Konzo disease [29], we applied the more appropriate approaches to highlight different biological patterns occurring between microorganisms and metabolites. We presented the exact workflow in the Konzo data analysis section and Figure S26.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our systematic evaluation of strategies to jointly analyze microbiome and metabolome data has permitted the illustration of the best methods depending on the research question. Thus, through an application on metabolomics and metagenomics data of the Konzo disease [29], we applied the more appropriate approaches to highlight different biological patterns occurring between microorganisms and metabolites. We presented the exact workflow in the Konzo data analysis section and Figure S26.…”
Section: Resultsmentioning
confidence: 99%
“…Our systematic evaluation of strategies to jointly analyze microbiome and metabolome data has permitted the illustration of the best methods depending on the research question. Thus, through an application on metabolomics and metagenomics data of the Konzo disease [29],…”
Section: Real-data Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bramble et al used shotgun metagenomic sequencing to perform a large-scale comparison of gut microbiome profiles in 180 children (from the urbanized capital Kinshasa to extreme rural areas in the southwest of the Democratic Republic of the Congo, including children affected by Konzo disease from prone villages). It was found that the intestinal microbiome structure varied greatly in different regions, but there was no significant difference in intestinal microbiome or functional enrichment between konzo-prone regions [ 44 ]. Yan et al characterized the intestinal microbiota of the population from 14 regions in one province and found that the influence of region on intestinal microbiota was much greater than other factors, and regional differences affected the cross-regional application of disease models [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial studies usually perform global hypothesis tests to explore the association between the microbiome and host phenotype, where the type of phenotype is determined by the distribution it follows, for example, Gaussian (BMI), Bernoulli (health/disease) and multinomial distribution (health/moderate disease/severe disease). Adonis [23] and ANOSIM [24,25] are classic distance-based statistical methods widely used to detect the association between the microbiome and host phenotypes in most microbial studies [26][27][28][29]. However, the disadvantage of these methods is that they do not adequately consider the effects of confounding factors, resulting in power loss.…”
Section: Introductionmentioning
confidence: 99%